Randomised controlled trial of mammographic screening in women from age 40: predicted mortality based on surrogate outcome measures - Moss, S (Nature Publishing Group, 2005)
A trial in the UK to study the effect on mortality from breast cancer of invitation for annual mammography from the age of 40–41, has randomised a total of 160 921 women in the ratio 1 : 2 to the intervention and control arms. All breast cancers diagnosed in the two arms have been identified, and the histology reviewed. This paper presents the results of an interim analysis using surrogate outcome measures to compare predicted breast cancer mortality in the two arms based on 1287 cases diagnosed to 31.12.1999. Due to earlier diagnosis, there is currently an 8% excess of invasive breast cancers in the intervention arm. The ratio of predicted deaths at 10 years in the intervention arm relative to the control arm, adjusted for this excess diagnosis, ranges from 0.89 (95% confidence interval (CI) 0.78–1.01) to 0.90 (95% CI 0.80–1.01). Screening from age 40 may result in a lower reduction in breast cancer mortality than that observed in other trials including women below age 50. This analysis based on surrogate outcome measures suggests that a reduction in breast cancer mortality may be observed in this trial. However, a number of assumptions have been necessary and firm conclusions must await the analysis of observed mortality from breast cancer.